Nonoperative Treatment of Appendicitis during Pregnancy in a Remote Area - Anne-Kathrine Carstens; Lise Fensby; Luit Penninga (Thieme Medical Publishers, Inc., 2018)
Appendicitis is the most common nonobstetric surgical disease during pregnancy. Appendicitis during pregnancy is associated with an increased risk of morbidity and perforation compared with the general population. Furthermore, it may cause preterm birth and fetal loss, and quick surgical intervention is the established treatment option in pregnant women with appendicitis. In Greenland, geographical distances are very large, and weather conditions can be extreme, and surgical care is not always immediately available. Hence, antibiotic treatment is often initiated as a bridge-to-surgery. We report on a pregnant Greenlandic Inuit woman with appendicitis who was treated with intravenous antibiotics. Antibiotic treatment was successful before surgical care became available and the patient was not operated. No complications occurred, and further pregnancy was uneventful. Our case suggests that antibiotic treatment of appendicitis during pregnancy as a bridge-to-surgery may be a sensible treatment option in remote areas, where no surgical care is immediately available. In some cases, antibiotic treatment may turn out to be definitive treatment.